A possibilidade de aplicação no Direito do Trabalho do princípio constitucional da proporcionalidade para efetivação dos direitos fundamentais - Guimaraes, Ricardo Pereira de Freitas (2014)
The present study aims to elucidate some extent about the principle of proportionality inserted in a contributory process of solving social conflicts in the procedural context. To attempt an approximation of its use safely we move first seeking their historical origin, which was mainly in Germany, starting with discussions occurred between the leading scholars of the subject, especially philosophers and students of law like Robert Alexy and Ronald Dworkin. Advance our purpose in trying to demonstrate that the advancement of social relations - both in its today's globalized texture as the birth of new social relations every day, especially in labor law - does not allow more in aall circumstances the application of the simply positivism, the society cries out for an immediate response, which can occur in certain circumstances by applying the principle of proportionality, in particular when dealing with fundamental rights, now entering in a post-positivist view. We try to exemplify through national and international decisions with individual cases the correct application of the principle, not with a critical tone, but in order to present an overview of its applicability within the contours developed at the Work. We point to situations that are already present on the day of the Labour Court regarding collisions of fundamental rights, showing the position of national and International scholars. We present a historical development of constitutional rights related to labor law, still trying to show that some questions on a simple subsumption of the fact in the norm does not present enough to solve the current social relationships in the field of labor law, especially when involved fundamental constitutional rights. 10 We venture to some extent, to question the applicability of certain principles relaciones between employee X employer relationship, to its current incompleteness for any situation. We also Question in a pontual and exemplary manner some decisions of the Superior Labor Court, which in our experience, do not reflects in a rigjt wau the principle of proportionality because the movement said constitutionalization of rights. The result of the work leads us to thinking that there is clearly a need for a breakthrough, especially in how to interpret the collision of fundamental rights for accurate delivery of relief sought by society in conflict zones of such rights